Comment on the relationship between electrical and optical conductivity used in several recent papers published in the journal of materials science: materials in electronics - Aly, Kamal A. (Journal of materials science. Materials in electronics, 2022)
Recently a series of papers have been published in the Journal of Materials Science: Materials in Electronics and also in other journals in which a relationship of the form σ el = 2 k n c / α , σ el = 2 λ σ op / α and σ el = λ nc / ( 2 π ) (where λ is the free-space wavelength of light c is the speed of light in vacuum) between the electrical conductivity σ el and optical conductivity σ 1op . The  refractive index n , absorption coefficient α and the extinction coefficient k have been used and conclusions have been drawn from these relationships, including graphs of electrical and optical conductivity as a function of photon energy over a very wide range (e.g., 1–5.6 eV). In this comment, the difference between the optical ( σ op ) and electrical ( σ el ) conductivities is considered and analyzed through well-known textbook considerations; correct relations are given, and it is shown that the above expressions that have recently appeared in the literature are incorrect.